Forensic implications of the variation in morphology of marginal serrations on the teeth of the great white shark - Nambiar, P.; Brown, K.A.; Bridges, T.E. (1996)
The teeth of the Great White Shark have been examined to ascertain whether there is any commonality in the arrangement or number of the marginal serrations (peaks) or, indeed, whether individual sharks have a unique pattern of shapes or size of the peaks. The teeth of the White Shark are characteristic in size and shape with serrations along almost the entire mesial and distal margins. This study has revealed no consistent pattern of size or arrangement of the marginal serrations that was sufficiently characteristic within an individual shark to serve as a reliable index of identification of a tooth as originating from that particular shark. Nonetheless, the serrations are sufficiently distinctive to enable the potential identification of an individual tooth as having been the cause of a particular bitemark.